(untitled) (Journal of Computational Mathematics, 2006)
The n-divided difference of the composite function h:=f° g of functions f, g at a group of nodes t_0, t_1, …, t_n is shown by the combinations of divided differences of f at the group of nodes g(t_0), g(t_1), …, g(t_m) and divided differences of g at several partial group of nodes t_0, t_1,…, t_n, where m=1, 2,…, n. Especially, when the given group of nodes are equal to each other completely, it will lead to Faà di Bruno's formula of higher derivatives of function h.